Preparation method of heterojunction solar cell printing screen
By using a composite film of fluoropolyimide and zinc oxide nanorods in the heterojunction solar cell printing screen, the problems of insufficient adhesion and light transmittance of the conductive paste are solved, and printing efficiency and battery performance are improved.
Patent Information
- Application Number
- CN202411391364.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-08
AI Technical Summary
The adhesion of conductive paste during screen printing of existing heterojunction solar cells leads to blockage of screen printing, insufficient light transmittance and ultraviolet resistance, affecting printing efficiency and battery photoelectric conversion efficiency.
A polymer film containing fluorine polyimide as the matrix is used, and zinc oxide nanorods are deposited on its surface to form a composite film, reducing the adhesion of conductive paste, and improving light transmittance and ultraviolet resistance.
It significantly improves the light transmittance and UV resistance of the printed screen, reduces the amount of conductive paste, improves the photoelectric conversion efficiency and production efficiency of heterojunction solar cells, and extends the service life of the printed screen.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of printed screens, and in particular to a method for preparing a printed screen for a heterojunction solar cell. Background Art
[0002] With the continuous development of science and technology and economy, energy issues have become a key issue for the progress and development of human society. At present, the world still mainly uses non-renewable energy, such as oil, coal, natural gas, etc. These energy sources are not only non-renewable, but also produce a large amount of carbon dioxide, nitrogen dioxide, sulfur dioxide and dust during use, which will seriously endanger the environment of society.
[0003] Solar energy is a very abundant renewable and green energy source that can provide enough energy to meet the needs of the whole world. It has become the focus of research in various countries. Therefore, solar energy using photovoltaic power generation technology has good application scenarios. As the most promising energy collection device based on the photovoltaic effect, solar cells can effectively convert sunlight into electrical energy, and solar cell technology has developed rapidly in recent decades. Heterojunction solar cells not only have high conversion efficiency and high open circuit voltage, but also have the advantages of low temperature coefficient and low preparation process temperature.
[0004] Screen printing technology is required in the preparation of heterojunction solar cells. The conductive paste used in the screen printing process has high viscosity and often adheres to the surface of the screen, causing the screen to be clogged and affecting its printing life. In addition, the pattern film on the current printing screen has shortcomings such as poor light transmittance and poor UV resistance, which in turn affects the printing efficiency and the photoelectric conversion efficiency of the battery. Summary of the invention
[0005] The technical problem to be solved by the present invention is: in view of the shortcomings of the prior art, a method for preparing a heterojunction solar cell printing screen is provided, wherein the film with a pattern in the method is based on a fluorinated polyimide and zinc oxide nanorods are deposited on its surface. The composite film prepared by the above structure not only has a high light transmittance, but also has excellent UV resistance and good hydrophobicity, and can effectively reduce its adhesion to the conductive paste, reduce the amount of the conductive paste to a certain extent, and improve the photoelectric conversion efficiency of the heterojunction solar cell.
[0006] In order to solve the above technical problems, the technical solution of the present invention is:
[0007] A method for preparing a heterojunction solar cell printing screen, comprising the following steps:
[0008] S1: preparing a polymer film, etching a pattern on the polymer film, and obtaining a polymer film with a pattern;
[0009] S2: Adhesive is used to bond the polymer film with the pattern to the blank screen to obtain a printing screen.
[0010] Preferably, in step S1, the polymer film is a polyimide / zinc oxide composite film, and the preparation method thereof comprises the following steps:
[0011] (1) adding 4,4'-(hexafluoroisopropyl)bis(p-phenyloxy)diphenylamine and 6FDA to dimethylacetamide, stirring at room temperature, to prepare a spinning solution;
[0012] (2) preparing the spinning solution into a polyimide film by an electrospinning process;
[0013] (3) dissolving zinc acetate dihydrate in ethanol to obtain a metal salt solution, dissolving sodium hydroxide in ethanol to obtain an alkaline solution, and adding the alkaline solution dropwise to the metal salt solution while stirring, and continuing to stir after the addition is completed to obtain a zinc-containing sol;
[0014] (4) placing the polyimide film in a zinc-containing sol for ultrasonic treatment, then taking out the film and drying it to obtain a film containing a seed layer;
[0015] (5) The seed layer-containing film is immersed in a zinc oxide precursor solution, and the film is taken out, washed, and dried to obtain a polyimide / zinc oxide composite film.
[0016] Preferably, in step (1), the molar ratio of 4,4'-(hexafluoroisopropyl)bis(p-phenyloxy)diphenylamine to 6FDA is 1:(1-2); the stirring treatment time at room temperature is 10-20 hours; and the solid content of the spinning solution is 10-20%.
[0017] Preferably, in step (2), the conditions for electrospinning are a spinning voltage of 10-20 kV, a receiving distance of 20 cm, and a propulsion speed of 0.06 mm / min.
[0018] Preferably, step (2) also includes drying and heat treating the film on the collector.
[0019] Preferably, in step (2), the heat treatment conditions are: nitrogen atmosphere, heat treatment at 200° C. for 5-6 hours.
[0020] Preferably, in step (3), the concentration of the metal salt solution is 0.02-0.03 g / ml, the concentration of the alkaline solution is 0.01-0.02 g / ml, and the volume ratio of the metal salt solution to the alkaline solution is 1:(1-1.5).
[0021] Preferably, in step (3), after the dropwise addition is completed, the stirring treatment is continued at a temperature of 60° C. for 1-2 h.
[0022] Preferably, in step (4), the power of the ultrasonic treatment is 200-500 W, and the time is 3-5 min; the drying is carried out at 80° C. for 5-10 min and at 120-150° C. for 3-5 min.
[0023] Preferably, in step (5), the zinc oxide precursor solution is a mixed aqueous solution of zinc nitrate and hexamethylenetetramine, and the concentrations of zinc nitrate and hexamethylenetetramine in the mixed aqueous solution are 0.02-0.03 mol / L and 0.02-0.03 mol / L, respectively.
[0024] Preferably, in step (5), the immersion treatment temperature is 80-90°C for 1-2 hours, and the drying temperature is 150-200°C for 3-4 hours.
[0025] Preferably, in step S2, the adhesive comprises epoxy resin, defoaming agent and leveling agent, and the mass ratio of the three is 1:(0.01-0.02):(0.01-0.02); the thickness of the adhesive is 2-10 microns.
[0026] Preferably, the epoxy resin is a bisphenol A epoxy resin, the defoamer is a polyether defoamer, and the leveling agent is a polyether leveling agent.
[0027] Preferably, the blank screen includes a screen frame and a mesh cloth arranged on the screen frame, the warp of the mesh cloth is a stainless steel wire with a wire diameter of 5-10 microns, the weft is a tungsten wire with a wire diameter of 5-10 microns, and the mesh number of the mesh cloth is 400-600 meshes.
[0028] Preferably, the tension of the blank screen is 8-25kg / cm 2 .
[0029] Preferably, the temperature during bonding is 120° C.-220° C., the pressure is 0.1 MPa-10 MPa, and the curing time is 10-60 min.
[0030] Preferably, the pattern is etched by laser cutting, and the laser energy, laser wavelength and laser frequency are selected according to the thickness of the composite film to be cut, wherein the laser is selected based on the ability to completely cut the composite film.
[0031] Due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0032] The printing screen of the present invention is prepared by combining a layer of polymer film with a pattern on a blank screen. The polymer film not only has good light transmittance, but also has excellent UV resistance, good hydrophobicity, and poor adhesion to the conductive paste. It can effectively avoid the conductive paste adhering to the surface of the printing screen during the printing process, resulting in paste waste and screen clogging.
[0033] The printing screen prepared by the present invention has the advantages of high light transmittance, high UV resistance and the like. High light transmittance can improve the utilization efficiency of light, thereby significantly improving the curing rate of the photocurable material during the printing process, thereby improving the production efficiency and product quality of the battery. High UV resistance effectively improves the stability and durability of the printing screen.
[0034] The polymer film used in the present invention is based on fluorinated polyimide as a matrix, and then a layer of zinc oxide nanorods is in situ grown on its surface. The fluorinated groups in the above film and the highly disordered microstructure ZnO nanorods are conducive to reducing the surface energy, thereby giving the film a hydrophobic surface. In addition, the fluorinated polyimide has good chemical stability and heat resistance, and the fluorine atoms in its molecular structure can reduce the light absorption of the polymer, which helps to improve the light transmittance. The structure of the zinc oxide nanorods has good optical transparency, especially in the visible light band. Therefore, through the combination of the two, a film material with high light transmittance is obtained. Moreover, in the polymer film material of the present invention, the fluorinated polyimide has a low absorption of ultraviolet rays and can effectively block and scatter ultraviolet rays, while the zinc oxide nanorods will generate electron-hole pairs under ultraviolet irradiation, which can effectively neutralize the free radicals caused by ultraviolet rays, thereby reducing the light damage of the material. DETAILED DESCRIPTION
[0035] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
[0036] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.
[0037] Unless otherwise specified, the materials in the following examples and comparative examples are commercially available.
[0038] Unless otherwise specified, the conditions in the following examples and comparative examples are conventional conditions in the art.
[0039] The blank screen described in the following embodiments and comparative examples includes a screen frame and a mesh cloth arranged on the screen frame, wherein the warp of the mesh cloth is a stainless steel wire with a wire diameter of 5 microns, the weft is a tungsten wire with a wire diameter of 5 microns, and the mesh number of the mesh cloth is 400 meshes; the tension of the blank screen plate when stretching the screen is 20kg / cm 2 .
[0040] Example 1
[0041] A method for preparing a heterojunction solar cell printing screen, comprising the following steps:
[0042] (1) 3 mmol 4,4'-(hexafluoroisopropyl)bis(p-phenyloxy)diphenylamine and 3 mmol 6FDA were added to N,N-dimethylacetamide, and stirred at room temperature for 20 hours to obtain a spinning solution with a solid content of 15%; an electrospinning process (spinning voltage of 15 kV, receiving distance of 20 cm, and propulsion speed of 0.06 mm / min) was used for spinning, and the film deposited on the collector was dried at 70°C for 20 hours, and then treated at 200°C in a nitrogen atmosphere to obtain a polyimide film with a thickness of 10 μm;
[0043] (2) adding a 0.02 g / ml sodium hydroxide ethanol solution dropwise to a 0.02 g / ml zinc acetate dihydrate ethanol solution under stirring at 60° C. and 1000 rpm (the volume ratio of the sodium hydroxide ethanol solution to the zinc acetate dihydrate ethanol solution is 1:1), and stirring is continued for 1 hour after the addition is completed to obtain a zinc-containing sol;
[0044] (3) immersing the polyimide film into the zinc-containing sol, ultrasonically treating the film at 200 W for 5 min, taking out the film, and then drying the film at 80° C. for 6 min and at 150° C. for 5 min to obtain a film containing a seed layer;
[0045] (4) placing the above-mentioned seed layer-containing film in 50 ml of zinc oxide precursor solution (a mixed aqueous solution of zinc nitrate and hexamethylenetetramine, the concentrations of zinc nitrate and hexamethylenetetramine in the mixed aqueous solution are 0.02 mol / L and 0.02 mol / L, respectively), immersing at 90° C. for 2 h, then cooling to room temperature, taking out the film, washing it, and then drying it at 80° C. for 50 min, and finally keeping it at 200° C. for 3 h to obtain a polymer film;
[0046] (5) cutting a preset pattern on the polymer film using a laser cutting process to obtain a polymer film with a pattern;
[0047] (6) Adhesive (bisphenol A epoxy resin, polyether defoaming agent, polyether leveling agent in a mass ratio of 1:0.01:0.01) is used to bond the polymer film with the pattern to the blank screen. The thickness of the adhesive is controlled to be 5 μm. The adhesive is cured at a temperature of 150° C. and a pressure of 2 MPa for 30 min to obtain a printing screen.
[0048] Example 2
[0049] (1) 3 mmol 4,4'-(hexafluoroisopropyl)bis(p-phenyloxy)diphenylamine and 3 mmol 6FDA were added to N,N-dimethylacetamide, and stirred at room temperature for 20 hours to obtain a spinning solution with a solid content of 15%; an electrospinning process (spinning voltage of 15 kV, receiving distance of 20 cm, and propulsion speed of 0.06 mm / min) was used for spinning, and the film deposited on the collector was dried at 70°C for 20 hours, and then treated in a nitrogen atmosphere at 200°C to obtain a polyimide film with a thickness of 15 μm;
[0050] (2) adding a sodium hydroxide ethanol solution having a concentration of 0.02 g / ml dropwise to a zinc acetate dihydrate ethanol solution having a concentration of 0.02 g / ml under stirring at 60° C. and 1000 rpm (the volume ratio of the sodium hydroxide ethanol solution to the zinc acetate dihydrate ethanol solution is 1:1), and stirring is continued for 1.5 h after the addition is completed to obtain a zinc-containing sol;
[0051] (3) immersing the polyimide film into the zinc-containing sol, ultrasonically treating the film at 200 W for 5 min, taking out the film, and then drying the film at 80° C. for 6 min and at 150° C. for 5 min to obtain a film containing a seed layer;
[0052] (4) placing the above-mentioned seed layer-containing film in 50 ml of zinc oxide precursor solution (a mixed aqueous solution of zinc nitrate and hexamethylenetetramine, the concentrations of zinc nitrate and hexamethylenetetramine in the mixed aqueous solution are 0.02 mol / L and 0.02 mol / L, respectively), immersing at 90° C. for 2 h, then cooling to room temperature, taking out the film, washing it, and then drying it at 80° C. for 50 min, and finally keeping it at 200° C. for 3 h to obtain a polymer film;
[0053] (5) cutting a preset pattern on the polymer film using a laser cutting process to obtain a polymer film with a pattern;
[0054] (6) Adhesive (bisphenol A epoxy resin, polyether defoaming agent, polyether leveling agent in a mass ratio of 1:0.01:0.01) is used to bond the polymer film with the pattern to the blank screen. The thickness of the adhesive is controlled to be 5 μm. The adhesive is cured at a temperature of 180° C. and a pressure of 6 MPa for 30 min to obtain a printing screen.
[0055] Example 3
[0056] (1) 3 mmol 4,4'-(hexafluoroisopropyl)bis(p-phenyloxy)diphenylamine and 3 mmol 6FDA were added to N,N-dimethylacetamide, and stirred at room temperature for 20 hours to obtain a spinning solution with a solid content of 15%; an electrospinning process (spinning voltage of 15 kV, receiving distance of 20 cm, and propulsion speed of 0.06 mm / min) was used for spinning, and the film deposited on the collector was dried at 70°C for 20 hours, and then treated at 200°C in a nitrogen atmosphere to obtain a polyimide film with a thickness of 20 μm;
[0057] (2) adding a sodium hydroxide ethanol solution having a concentration of 0.02 g / ml dropwise to a zinc acetate dihydrate ethanol solution having a concentration of 0.02 g / ml under stirring at 60° C. and 1000 rpm (the volume ratio of the sodium hydroxide ethanol solution to the zinc acetate dihydrate ethanol solution is 1:1), and stirring is continued for 2 h after the dropwise addition is completed to obtain a zinc-containing sol;
[0058] (3) immersing the polyimide film into the zinc-containing sol, ultrasonically treating the film at 200 W for 5 min, taking out the film, and then drying the film at 80° C. for 6 min and at 150° C. for 5 min to obtain a film containing a seed layer;
[0059] (4) placing the above-mentioned seed layer-containing film in 50 ml of zinc oxide precursor solution (a mixed aqueous solution of zinc nitrate and hexamethylenetetramine, the concentrations of zinc nitrate and hexamethylenetetramine in the mixed aqueous solution are 0.02 mol / L and 0.02 mol / L, respectively), immersing at 90° C. for 2 h, then cooling to room temperature, taking out the film, washing it, and then drying it at 80° C. for 50 min, and finally keeping it at 200° C. for 3 h to obtain a polymer film;
[0060] (5) cutting a preset pattern on the polymer film using a laser cutting process to obtain a polymer film with a pattern;
[0061] (6) Adhesive (bisphenol A epoxy resin, polyether defoaming agent, polyether leveling agent in a mass ratio of 1:0.01:0.01) is used to bond the polymer film with the pattern to the blank screen. The thickness of the adhesive is controlled to be 5 μm. The adhesive is cured at a temperature of 200° C. and a pressure of 8 MPa for 40 minutes to obtain a printing screen.
[0062] Example 4
[0063] (1) 3 mmol 4,4'-(hexafluoroisopropyl)bis(p-phenyloxy)diphenylamine and 3 mmol 6FDA were added to N,N-dimethylacetamide, and stirred at room temperature for 20 hours to obtain a spinning solution with a solid content of 15%; an electrospinning process (spinning voltage of 15 kV, receiving distance of 20 cm, and propulsion speed of 0.06 mm / min) was used for spinning, and the film deposited on the collector was dried at 70°C for 20 hours, and then treated at 200°C in a nitrogen atmosphere to obtain a polyimide film with a thickness of 20 μm;
[0064] (2) adding a sodium hydroxide ethanol solution having a concentration of 0.02 g / ml dropwise to a zinc acetate dihydrate ethanol solution having a concentration of 0.02 g / ml under stirring at 60° C. and 1000 rpm (the volume ratio of the sodium hydroxide ethanol solution to the zinc acetate dihydrate ethanol solution is 1:1), and stirring is continued for 2 h after the dropwise addition is completed to obtain a zinc-containing sol;
[0065] (3) immersing the polyimide film into the zinc-containing sol, ultrasonically treating the film at 200 W for 5 min, taking out the film, and then drying the film at 80° C. for 6 min and at 150° C. for 5 min to obtain a film containing a seed layer;
[0066] (4) placing the above-mentioned seed layer-containing film in 50 ml of zinc oxide precursor solution (a mixed aqueous solution of zinc nitrate and hexamethylenetetramine, the concentrations of zinc nitrate and hexamethylenetetramine in the mixed aqueous solution are 0.02 mol / L and 0.02 mol / L, respectively), immersing at 90° C. for 2 h, then cooling to room temperature, taking out the film, washing it, and then drying it at 80° C. for 50 min, and finally keeping it at 200° C. for 3 h to obtain a polymer film;
[0067] (5) cutting a preset pattern on the polymer film using a laser cutting process to obtain a polymer film with a pattern;
[0068] (6) Adhesive (bisphenol A epoxy resin, polyether defoaming agent, polyether leveling agent in a mass ratio of 1:0.01:0.01) is used to bond the polymer film with the pattern to the blank screen. The thickness of the adhesive is controlled to be 5 μm. The adhesive is cured at a temperature of 220° C. and a pressure of 10 MPa for 60 min to obtain a printing screen.
[0069] In order to better verify that the printing screen prepared by the present invention has excellent performance, the following is a detailed description in combination with multiple comparative examples with reference to Example 1.
[0070] Comparative Example 1
[0071] Compared with Example 1, the difference is that the polymer film is a pure polyimide film, zinc oxide nanorods are not grown on the surface thereof, and other conditions are the same as those in Example 1.
[0072] After testing, the tensile strength of the polymer film prepared in the above embodiment is as high as 4.0 MPa, and the tensile strength of the pure polyimide film of comparative example 1 is 2.0 MPa; the light transmittance of the polymer film in the embodiment within the wavelength range of 280 to 400 nm is close to 0%, while the light transmittance of the film in comparative example 1 within the wavelength range of 280 to 400 nm is 20%. Compared with the comparative example, the polymer film of the present invention has better anti-ultraviolet ability.
[0073] The average transmittance of the polymer film prepared in the example is as high as 95.8% within the range of 400-1100 nm, while the average transmittance of the film in comparative example 1 is 85.6% within the range of 400-1100 nm.
[0074] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.
Claims
1. A method for preparing a heterojunction solar cell printing screen, characterized in that: The following steps are involved: S1: preparing a polyimide / zinc oxide composite film, etching a pattern on the polyimide / zinc oxide composite film, and obtaining a polymer film with a pattern; S2: Adhesive is used to bond the polymer film with the pattern to the blank screen to obtain a printing screen.
2. The method for preparing a heterojunction solar cell printing screen according to claim 1, characterized in that: In step S1, the method for preparing the polyimide / zinc oxide composite film comprises the following steps: (1) adding 4,4'-(hexafluoroisopropyl)bis(p-phenyloxy)diphenylamine and 6FDA to dimethylacetamide, stirring at room temperature, to prepare a spinning solution; (2) preparing the spinning solution into a polyimide film by an electrospinning process; (3) dissolving zinc acetate dihydrate in ethanol to obtain a metal salt solution, dissolving sodium hydroxide in ethanol to obtain an alkaline solution, and adding the alkaline solution dropwise to the metal salt solution while stirring, and continuing to stir after the addition is completed to obtain a zinc-containing sol; (4) placing the polyimide film in a zinc-containing sol for ultrasonic treatment, then taking out the film and drying it to obtain a film containing a seed layer; (5) The seed layer-containing film is immersed in a zinc oxide precursor solution, and the film is taken out, washed, and dried to obtain a polyimide / zinc oxide composite film.
3. The method for preparing a heterojunction solar cell printing screen according to claim 2, characterized in that: In step (1), the molar ratio of 4,4'-(hexafluoroisopropyl)bis(p-phenoxy)diphenylamine to 6FDA is 1:(1-2); and / or the stirring treatment time at room temperature is 10-20 hours; and / or the solid content of the spinning solution is 10-20%.
4. The method for preparing a heterojunction solar cell printing screen according to claim 2, characterized in that: In step (2), the conditions for electrospinning are a spinning voltage of 10-20 kV, a receiving distance of 20 cm, and a propulsion speed of 0.06 mm / min.
5. The method for preparing a heterojunction solar cell printing screen according to claim 2, characterized in that: Step (2) also includes drying and heat treating the thin film on the collector; the heat treatment conditions are nitrogen atmosphere, heat treatment at 200°C for 5-6 hours.
6. The method for preparing a heterojunction solar cell printing screen according to claim 2, characterized in that: In step (3), the concentration of the metal salt solution is 0.02-0.03 g / ml, the concentration of the alkaline solution is 0.01-0.02 g / ml, and the volume ratio of the metal salt solution to the alkaline solution is 1:(1-1.5); and / or the temperature for continuing stirring after the dropwise addition is 60° C. for 1-2 h; and / or the power of the ultrasonic treatment is 200-500 W for 3-5 min; and / or the drying is sequentially carried out at 80° C. for 5-10 min and at 120-150° C. for 3-5 min.
7. The method for preparing a heterojunction solar cell printing screen according to claim 2, characterized in that: In step (5), the zinc oxide precursor solution is a mixed aqueous solution of zinc nitrate and hexamethylenetetramine, and the concentrations of zinc nitrate and hexamethylenetetramine in the mixed aqueous solution are 0.02-0.03 mol / L and 0.02-0.03 mol / L, respectively; and / or the immersion treatment temperature is 80-90°C for 1-2 hours. The drying temperature is 150-200°C for 3-4 hours.
8. The method for preparing a heterojunction solar cell printing screen according to claim 1, characterized in that: In step S2, the adhesive includes epoxy resin, defoamer and leveling agent, and the mass ratio of the three is 1: (0.01-0.02): (0.01-0.02); the thickness of the adhesive is 2-10 microns; the epoxy resin is bisphenol A epoxy resin, the defoamer is a polyether defoamer, and the leveling agent is a polyether leveling agent.
9. The method for preparing a heterojunction solar cell printing screen according to claim 1, characterized in that: The blank screen includes a screen frame and a mesh cloth arranged on the screen frame. The warp of the mesh cloth is a stainless steel wire with a diameter of 5-10 microns, the weft is a tungsten wire with a diameter of 5-10 microns, and the mesh number of the mesh cloth is 400-600 meshes. The tension of the blank screen plate when stretching the screen is 8-25kg / cm 2 .
10. The method for preparing a heterojunction solar cell printing screen according to claim 1, characterized in that: The temperature when bonding together is 120°C-220°C, the pressure is 0.1MPa-10MPa, and the curing time is 10-60min.
Citation Information
Patent Citations
Colorless and transparent polyimide nano-composite material membrane and preparation method thereof
CN101831175A
Polyimide / zinc oxide composite lithium ion battery diaphragm and preparation method thereof
CN113725553A
Base material with transparent conductive film
JP2011029037A
Heated ceramic faceplate
KR1020190121258A
Plate making for printing electrode of solar cell and manufacturing method thereof
KR102424465B1